Recent Advances In Topical Therapy In Dermatology - Mohan Thappa Devinder (Wolters Kluwer Medknow Publications, 2003)
With changing times various newer topical agents are introduced in the field of dermatology. Tacrolimus and pimecrolimus are immunisuppressants, which are effective topically and are tried in the management of atopic dermatitis as well as other disorders including allergic contact dermatitis, atrophic lichen planus, pyoderma gangrenosum. Imiquimod, an immune response modifier, is presently in use for genital warts but has potentials as anti- tumour agent and in various other dermatological conditions when used topically. Tazarotene is a newer addition to the list of topical reginoids, which is effective in psoriasis and has better effect in combination with calcipotriene, phototherapy and topical costicosteroids. Tazarotene and adapelene are also effective in inflammatory acne. Calcipotriol, a vitamin D analogue has been introduced as a topical agent in the treatment of psoriasis. Steroid components are also developed recently which will be devoid of the side effects but having adequate anti-inflammatory effect. Topical photodynamic therapy has also a wide range of use in dermatology. Newer topical agents including cidofovir, capsaicin, topical sensitizers, topical antifungal agents for onychomycosis are also of use in clinical practice. Other promising developments include skin substitutes and growth factors for wound care.